Respuesta :

5x^2+3xy-25x-15y= 5x^2-25x+3xy-15y=
5x(x-5)+3y(x-5)=
= (x-5)(5x+3y)
lvvies

Answer:

(5x + 3x) (x -5)

Step-by-step explanation:

Factor a GCF from the expression, if possible.

Factor a Trinomial, if possible.

Factor a Difference Between Two Squares as many times as possible.

If the equation is in the form a2-b2, factor it to (a+b)(a-b). Equations with two variables factor differently than basic quadratics. For any equation a2-b2 where a and b do not equal 0, the equation factors to (a+b)(a-b). For example, the equation 9x2 - 4y2 = (3x + 2y)(3x - 2y).